The legal research: is it viable? - Bermúdez-Tapia, Manuel (2024)
In Peru, universities and research centres have assumed that research processes are carried out under standard conditions and can be planned and executed randomly, without a projection involving a progressive context over time. As a result, it is impossible to set concrete and tangible objectives that benefit society. In the legal field, the development, registration, and publication of research seem to lack a long-term purpose, as evidenced by the record of fewer than one hundred researchers in RENACYT. Given this scenario, the document's objective is to demonstrate the limited importance given to regulation, academic institutional work, and the evaluation of results in legal research in the country.